Increasing Adaptability Through Architectural Design - Alsibaai, Leyla; Özcan, Uğur (Tuncay Aydemir, 2022)
Since the advent of modernism's living machines and industrial revolution's mass housing, realizing the essentiality of adaptive architecture, architects have been experimenting and developing methods to create flexible architecture that can res-pond to changing needs. This paper sums up design approaches that relativley did last longer in architectural history. In which can be counted as: Open Plan, Indus-trialization and Prefabrication, Functional Uncertainty, Open Building and User Participation Design Approache. In order to design spaces that is inherently flexible and adaptable, it is beneficial to look back over the different methods experienced in the past centuries. However, it is not a necessity for us to reproduce the same spaces and tarred with the same brush. But rather than that developing or maybe mixing these design approaches. It can be said that there is no one truth or one right design approach to beleive in to accomplish flexibility, yet, it is important for the architect to choose the right method or maybe to mix methods that would be suitab-le for the place, people and time period designed for.

Modernizmin yaşam makinelerinin ve sanayi devriminin toplu konutlarının ortaya çıkmasından bu yana, uyarlanabilir mimarinin gerekliliğini fark eden mimarlar, de-ğişen ihtiyaçlara cevap verebilecek esnek mimari yaratmak için çeşitli yaklaşımlar deneyip geliştirimiştir. Bu makale, mimarlık tarihinde görece daha uzun süre daya-nan tasarım yaklaşımları özetlenmektedir. Bunlar, Açık Plan, Sanayileşme ve Pre-fabrikasyon, Fonksiyonel Belirsizlik, Açık Yapı ve Kullanıcı Katılımlı Tasarım Yaklaşımı olarak kısaca sayılabilir. Yapısı gereği esnek ve uyarlanabilir mekanlar yaratmak adına, geçmiş yüzyıllarda geliştirilen farklı yöntemlere bakmakta fayda vardır. Ancak aynı yöntemler izlememiz ve aynı deneylerden tekrar geçmemiz ye-rine bu tasarım yaklaşımlarını geliştirmek veya belki karıştırmak daha doğru ola-caktır. Esnekliği sağlamak için inanılacak tek bir doğru veya izlenecek tek bir tasa-rım yaklaşımı olmadığı söylenebilir. Tasarlanan çağın, coğrafi konumun ve sosyal kesimin dikkate alınmasıyla birlikte mimarın doğru yöntemi seçmesi veya çeşitli yaklaşımları birleştirmesi önem arz etmektedir.
Uyarlanabilirlik Kapasitesini Arttıran Mimari Tasarım Yaklaşımları
Keywords: User Needs; Architectural Design Approaches; Felxibility; Adaptability; Kullanıcı Gereksinimleri; Mimari Tasarım Yaklaşımları; Esneklik; Uyarlanabilirlik